One health agriculture: Heat stress mitigation dilemma in agriculture - Edit Mikó; Gideon Adu Donyina; Wissem Baccouri; Violetta Tóth; Kovács Flórián; Ingrid Melinda Gyalai; Gizem Yüksel; Dávid Köteles; Vineet Srivastava; George Wanjala (One Health)
The concept of One Health was developed as a successful strategy for addressing global crises that impact the health of animals, humans, and plants. The agriculture industry is facing a huge dilemma due to climate change and the impacts of heat stress, which might pose a threat to mankind in the future. In order to enhance the management of heat stress in the agriculture sector (Agri-heat stress), we suggest implementing the One Health approach. This is because the existing methods employed to alleviate heat stress in both livestock and crop farming may have side-effects on the well-being of animals, plants, humans, and the ecosystem. This review article examines the “dilemma” of mitigating heat stress in animal and crop husbandry. It discusses the One Health approach to heat stress, including a recommended strategy for reducing Agri-heat stress using the One Health approach. The study also highlights the benefits of adopting the One Health approach in mitigating Agri-heat stress. In our opinion, the efficacy of the One Health Approach in reducing Agri-heat stress depends on the process of conceptualization. This process includes recognizing the issue or hypothesis, as well as incorporating cooperating teams in the creation of environmentally friendly approaches. The efficacy and challenges of implementing this notion arise from the precise coordination of resources and collaborators.